Peer Victimization and Psychosocial Adjustment among Children of Parents with Physical Disabilities in China: A Comparative Study - Zhang, Huiping (Journal of interpersonal violence, 2023)
This study investigated whether the children of parents with physical disabilities endured higher levels of peer victimization. Particularly, this study focused on the mediating effects of peer victimization in the relationships between parental disability and both the emotional symptoms and prosocial behaviors exhibited by their children. Data were obtained from a survey on health and mental health among children and adolescents from disadvantaged families. The survey was conducted by Renmin University of China from August to September 2018 using multistage probability sampling method. The sample in this study included 716 adolescents, of whom 390 had at least one parent with physical disabilities and reported more severe peer victimization. In contrast to respondents who did not have parents with physical disabilities, these adolescents experienced more emotional symptoms and engaged in fewer prosocial behaviors. Furthermore, the analysis showed that 15.16% of the total effect of parental disability on emotional symptoms was mediated by peer victimization, which had a nonsignificant mediating effect in the relationship between parental disability and prosocial behaviors. These findings can inform practitioners who aim to help children of parents with physical disabilities improve their coping strategies and social skills to manage peer relationships. Moreover, these results highlight the importance of establishing an inclusive school and community environment to reduce social stigma and peer victimization toward children from disadvantaged families.